Pressure, under pressure - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Mushrooms, nuts, wild fruits, medicinal plants, rattan, bamboo Since time immemorial the forest has been prized for its so-called non-timber products which add much value, on top of timber and paper pulp. But the time for rampant exploitation of...